The effect of a plant cultivating program conducted at a community mental health center on the functional remission of individuals with schizophrenia: A randomized controlled study - ŞİŞMAN, FATMA NEVİN (W B SAUNDERS CO-ELSEVIER INC, 2020)
Purpose: This study was conducted to determine the effect of a plant cultivating program carried out in a community mental health center (CMHC) on the functional remission levels of individuals with schizophrenia. Materials and methods: The study was carried out as experimental research in pretest-posttest with control group design. Eighty individuals being followed up and treated at two CMHCs were randomly assigned to an intervention and a control group. The plant cultivating program, containing a theoretical and a practical sequence, was conducted for six weeks in the intervention group. The effectiveness of the program was assessed with the Functional Remission of General Schizophrenia (FROGS) scale. Results: The individuals participating in the program registered a significant increase in their FROGS scale overall scores as compared to the control group following the program. After the program, the intervention group's social, health, daily skills and professional functioning posttest scores were significantly higher than those of the control group. Conclusion: The plant cultivating program applied to individuals with schizophrenia at the CMHCs positively resulted in an improvement in their functional remission. The nurse-led plant cultivating program conducted at the CMHCs was observed to be an effective and applicable program that would improve the social, health, daily skills and professional functioning of individuals with schizophrenia.
Keywords: Functional; Nurse; Remission; Plant; Schizophrenia